Information Technology in Improving the Quality of Public Services: E-Government System Analysis - Johansyah, Oky Nur Pratiwi (PINISI Discretion Review, 2024)
This research uses the method Narrative Literature Review to explore the implementation of information technology in improving the quality of public services, especially through e-Government systems, in Indonesia. The results and discussion of the cited literature show that the application of information technology has produced a number of significant impacts. First, the majority of local governments have demonstrated a commitment to adopting information technology to improve public services, such as through the creation of government applications and websites. Second, the technical and human resource capacity to support e-Government has increased in most local governments, with an increase in the number of skilled human resources in IT and training efforts undertaken. Third, the implementation of e-Government has provided added value in increasing public access to government services and increasing administrative efficiency. However, there are still challenges that need to be overcome, such as the low quality of human resources, low public awareness of the importance of technology-based public services, and budget limitations. To overcome these challenges, continuous efforts are needed to increase human resource capacity, increase outreach to the community, and adequate budget allocation. Thus, the implementation of e-Government in Indonesia has the potential to be more successful in improving the quality of public services.